Enclosure stories: narratives from Northamptonshire - McDonagh, Briony; Daniels, Stephen (Sage, 2012)
This paper rethinks and revises enclosure narratives, thickening the concept of enclosure by researching a particular place and period: the English Midland county of Northamptonshire in the period between the 16th and the 19th centuries. It argues that while many elements of the landscape were dramatically reshaped by enclosure, the parliamentary enclosures of the late 18th and early 19th centuries were nevertheless part of a much longer process of landscape change. The paper points to the complexities within enclosure thought and experience, drawing particular attention to individuals and groups – including female landowners, ordinary villagers and animals – too often entirely written out of the ‘enclosure story’.